O emprego de algoritmos como auxiliar na prescrição homeopática - Silva, Mariana Jully Medeiros da (2021)
Introduction: Homeopathy is a science that consists in administering infinitesimal doses of the medicine, avoiding the aggravation of the symptoms and awakening the organic reaction towards the cure, being a science supported by the Law of the Similar. This article demonstrates how the use of algorithms can contribute to the organization of ideas in the homeopathic prescription act. This justification is based on the difficulties encountered by the use of the Medical Material and the Homeopathic Repertoire in an attempt to facilitate the search for information to prescribe. Objective: This article aims to make the homeopathic prescription act simpler and more dynamic, as well as to promote and make more dynamic the prescription of homeopathic medicines by all health professionals who are qualified to practice. Method: for the elaboration of this article were selected theoretical references, published in written and electronic media, that fit in the proposed theme, in Portuguese and English. The research of the information and scientific articles used in this work was performed on the websites Pubmed, Google Scholar, Scielo, Science Direct, Ministry of Health website and Anvisa, using the following words and expressions: homeopathic medicine, homeopathic prescription, medical material, homeopathic repertorization, pharmaceutical prescription, algorithm, Homeopathy algorithm. The period of publication was not relevant. Results and conclusion: in the course of this study, it was observed that the development of algorithms enables the practical organization of the characteristic symptoms of a disease and the possible ways of choosing a suitable homeopathic medicine. It may be noted that the method proposed during the article does not require the use of much technology to be put into practice, it is sufficient that the prescriber has prior knowledge of the disease and the technique, since the algorithms will be used for the purpose of organizing, more clearly, the ideas of the prescriber for a better choice of the medicine.